Restaurações cerâmicas minimamente invasivas executadas por cirurgiões dentistas com diferentes níveis de experiência profissional: estudo clínico cego, longitudinal e prospectivo - Melo, Régis Alexandre da Cunha [UNESP] (2015)
Objective: To evaluate if the dentist experience can influence the survival rate of cemented anterior and/or posterior thin ceramic restorations. Materials and Methods: A total of 16 professionals with different expertise level with thin ceramic restorations were divided into four groups (n=4) - Group 1: up to 2 years of the graduation; Group 2: 2 to 5 years of graduation; Group 3: 5-10 years of graduation; Group 4: more than 10 years of graduation. All professionals have been educated and trained to follow the same clinical protocol, but were unaware of the research objectives. A single evaluator accompanied the clinical treatments performed in 24 patients, totaling 274 single restorations in lithium disilicate, 158 in the anterior region and 116 in the posterior distributed region among the arches, 186 in the maxillae and 88 in the jaw. The thickness of the ceramic varied between 0.3 mm and 4.0 mm. Minor complications that occurred during the execution of the protocols, the etching and the light curing times and the type of cement were recorded. The restorations were cemented with different cements according to the thickness of ceramic, which: Rely X U200 (n = 120), Rely X Veneer (n = 95) and Variolink® Veneer (n = 58); totaling 91 full crowns, 137 laminated with preparation and 46 laminated with no prepare. Clinical assessments were performed after the installation of the restorations and at the controls of 30, 180 and 360 days after the cementing period. The parameters for evaluation were based on the modified USPHS criteria, adapted to the study. It was deemed unsuccessful when there was fracture or loosening of the restorations. Fractures were replicated and submitted to fractographic analysis. Results: The least number of failures were observed in Group 2 (1 debonding), the largest number in Group 1 (5 fractures) and highest...